2020
DOI: 10.1055/s-0040-1701452
|View full text |Cite
|
Sign up to set email alerts
|

Medial Meniscus Scaffold Implantation in Combination with Concentrated Bone Marrow Aspirate Injection: Minimum 3-Year Follow-up

Abstract: AbstractThe objective of this study is to show the short-term clinical and radiological outcomes of concentrated bone marrow aspirate (CBMA) injection administered in combination with medial meniscus scaffold implantation. Twenty-three patients who received intra-articular CBMA injection in combination with polyurethane-based medial meniscus scaffold implantation were evaluated within the scope of this study. The International Knee Documentation Committee (IKDC) questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Three articles were further excluded being series of previously published data and two being case reports [44, 46, 47, 49, 57]. Thus, a total of 37 studies [2, 3, 5–14, 16, 20–23, 25, 30, 33, 36, 37, 39–42, 45, 48, 51–53, 55, 56, 59, 61–63] were finally included in the quantitative and qualitative analysis (a detailed study description is reported in Table 1). Seven of them were comparative studies: 2 randomized controlled trials and 5 prospective comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles were further excluded being series of previously published data and two being case reports [44, 46, 47, 49, 57]. Thus, a total of 37 studies [2, 3, 5–14, 16, 20–23, 25, 30, 33, 36, 37, 39–42, 45, 48, 51–53, 55, 56, 59, 61–63] were finally included in the quantitative and qualitative analysis (a detailed study description is reported in Table 1). Seven of them were comparative studies: 2 randomized controlled trials and 5 prospective comparative studies.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 6 cases were on the lateral side of the right knee. 3 Data accounts for 75% of damage. Meniscus damage is 1-3 years old.…”
Section: Methods Research Objectsmentioning
confidence: 99%
“…35 In addition, intraarticular and in situ concentrated bone marrow aspirate injection in combination with medial meniscus scaffold implantation demonstrated clinical improvement in all functions and pain scores. 36 Another unique, synthetic meniscus arthroplasty is the NUsurface Meniscus Implant.…”
Section: Table 1 International Meniscus Reconstruction Experts Forum ...mentioning
confidence: 99%